"I am not exaggerating, literally a monster … a Jekyll and Hyde type thing": Understanding the lived experience of adoptive fathers whose children display violence and aggression. Issue 1 (12th January 2023) - Barrow, Victoria; Grey, Ben; Essau, Cecilia
The caregiving of fathers, especially adoptive fathers, is currently under-researched. This study explored the experience of adoptive fathers whose children displayed aggression and violence. Six Parent Development Interviews from a larger study were analysed using an attachment-informed Interpretive Phenomenological Analysis. Attachment discourse analysis derived from the Meaning of the Child Interview (MotC) and Parental Reflective Functioning Scale acted as 'third voice' in dialogue with the researchers' and participants' to explore the fathers' experience interpersonally, in the context of their family relationships. Four superordinate themes were identified, with these fathers feeling 'The Problem is in the Child', at times sensing themselves persecuted by their child and lacking agency as a parent. 'Confusion and Comparison' highlighted the fathers' sense of helplessness and longing for the 'normal' family life they associated with being a biological parent. The fathers also talked of 'The Mixed Blessing of Feeling like a Father', expressing extremes of anger but also fondness for their children. Participants engaged in 'Looking Back' both at their child's trauma history and their own history of being parented, which in all but one father, also involved trauma. This left the fathers searching for answers to questions around biological versus relational origins of difficulties, and also pain arising from their own frustrated intention to create a better family life than they had experienced themselves in childhood. Common to all of this was the fathers' sense of helplessness in being unable to contain or influence their child's difficult behaviour, that negated or challenged their sense of fatherhood. We suggest a more relational approach that explicitly includes the father's past and present experience, rather than treating the child's aggressive behaviour in isolation. This could support fathers in recovering an internal experience of a shared relationship with, and being a father to, their adopted child.